The Tragic Revelation of the Transgender in “The Man Who Thought Himself a Woman” (Anonymous) - Ratna Asmarani (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2023)
The aim of this article is to analyze the tragic revelation of the transgender in an anonymous short story entitled “The Man Who Thought Himself a Woman.” The analysis is supported by the concepts of transgender and cross-dressing since the male main character who has a wife and two daughters gradually becomes a transgender preceded by becoming a secret cross-dresser. The library research method is used to collect the relevant data while the qualitative research method is used in the general analysis. The literary analysis is supported by textual research method focusing on character, conflict, and setting, and contextual research method focusing on the concepts of transgender and cross-dressing. The result shows that becoming transgender is a difficult process and needs much bravery. Since the main male character feels unable to face the consequence as a transgender, he starts by becoming a cross-dresser in secret at night for a couple of hours at the house basement. When he finally wants to declare in public about his coming out in a full female clothes, he prefers to present it as his last performance in his well-arranged death.